2015
DOI: 10.1113/jp270195
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric oxide in passive leg movement‐induced vasodilatation with age: insight from alterations in femoral perfusion pressure

Abstract: Key pointsr The passive leg movement (PLM) model is a novel approach to assess vascular function. r Increasing femoral perfusion pressure (FPP) by moving from the supine to the upright-seated posture augments the vasodilatory response to PLM in the young, with no effect in the old, but whether this augmented vasodilatation is nitric oxide (NO) dependent is unknown.r Using an intra-arterial infusion of N G -monomethyl-L -arginine ( L -NMMA) to inhibit nitric oxide synthase (NOS), the posture-induced increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 39 publications
3
75
0
Order By: Relevance
“…This PLM-induced hyperemia has previously been reported in both young and old men; however, the magnitude of the vasodilatory response to PLM is significantly attenuated with age (11,23). Recent investigations into the mechanisms responsible for the PLM response conclude that PLM-induced vasodilation is predominantly NO mediated in young men, as evidenced by an ϳ80 -90% reduction in the hyperemic response during intraarterial infusion of the NO synthase (NOS) inhibitor N Gmonomethyl-L-argenine (10,28,39). Furthermore, by once again using NOS inhibition, both Trinity et al (38) and Groot et al (10) reported that the attenuated PLM-induced vasodilation described in older men was a consequence of reduced NO bioavailability with age.…”
Section: Age and Supine Plm-induced Vasodilation In Womenmentioning
confidence: 93%
See 4 more Smart Citations
“…This PLM-induced hyperemia has previously been reported in both young and old men; however, the magnitude of the vasodilatory response to PLM is significantly attenuated with age (11,23). Recent investigations into the mechanisms responsible for the PLM response conclude that PLM-induced vasodilation is predominantly NO mediated in young men, as evidenced by an ϳ80 -90% reduction in the hyperemic response during intraarterial infusion of the NO synthase (NOS) inhibitor N Gmonomethyl-L-argenine (10,28,39). Furthermore, by once again using NOS inhibition, both Trinity et al (38) and Groot et al (10) reported that the attenuated PLM-induced vasodilation described in older men was a consequence of reduced NO bioavailability with age.…”
Section: Age and Supine Plm-induced Vasodilation In Womenmentioning
confidence: 93%
“…2). Additionally, the rapid vasodilatory response (slope of the increasing LVC over time for the first 9 s) to PLM, previously determined to be NO-independent in men in the supine posture (10,38), was also significantly attenuated with age in women (ϳ 70%; Fig. 4).…”
Section: Age and Supine Plm-induced Vasodilation In Womenmentioning
confidence: 96%
See 3 more Smart Citations